PERANAN PENDIDIKAN ORANG TUA DALAM MENINGKATKAN MUTU PENDIDIKAN AGAMA ANAK DI MADRASAH TSANAWIYAH NASYRUL ULUM PAMEKASAN - Supandi, Supandi (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2019)
The purpose of Islamic religious education is identical to the purpose of life of every human or Muslim. The implementation of education aims to humanize humans, glorify them because science utilizes reason with all its intelligence in order to achieve what it aspires to. Therefore, the success or failure of an educational process will also be influenced by the surrounding environment, namely the family in this case is the parents. Based on this background, the researcher is interested in examining the activities mentioned above. This research activity uses qualitative research with informants, the teachers are researchers who meet in the field, then guardians of students / parents and some students in the field. Based on the reviews in advance both through liberty research and fild research, it can be concluded as follows: 1) Parental education is the first and foremost education to humanize and socialize human children. 2) Education of parents as the smallest social unit provides basic stamps and foundations for the development and improvement of the quality of children's religious education. 3) Behavior in the family will give inpact or a contagious influence on the community environment.